The blackwell companion to globalization - Ritzer, George, Ed (Wiley blackwell, 2007)
This companion features original essays on the complexity of globalization and its diverse and sometimes conflicting effects. Written by top scholars in the field, it offers a nuanced and detailed examination of globalization that includes both positive and critical evaluations.